ANALISIS YURIDIS PERTANGGUNGJAWABAN PIDANA MALAPRAKTIK KEDOKTERAN YANG DILAKUKAN OLEH DOKTER DALAM PENANGANAN PASIEN COVID-19 DALAM HUKUM PIDANA INDONESIADIKAITKAN DENGAN KEADIILAN - Dhafa Dendy Dwijaya; Davit Rahmadan; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Malpractice is an act or bad practice, in other words, is a negligence (badpractice) on the part of professionals in carrying out their profession. Thus medicalmalpractice is an act of a doctor who is considered wrong when practicing medicine andviolating legal norms. Criminal liability is imposing a penalty on the maker for an actthat violates a prohibition or creates a prohibited situation. The formulation of theproblem in this study is how medical malpractice is regulated by doctors in handlingCovid-19 patients in Indonesian criminal law and how is criminal responsibility fordoctors who commit medical malpractice in handling Covid-19 patients in Indonesiancriminal law related to justice.The method in this study uses normative legal research methods. This research isalso referred to as library research or document study. It is referred to as research ordocument study because this research is mostly carried out on secondary data in thelibrary.From the results of this study, the first result was that, in Indonesian criminal law,there are no laws and regulations that specifically and in detail discuss medicalmalpractice, especially medical malpractice when a health emergency (pandemic)occurs, such as during Covid-19. Indonesian criminal law still uses existing laws andregulations such as the Criminal Code, Law No. 29 of 2004 concerning MedicalPractice, Law No. 36 of 2009 concerning Health, Law No. 44 of 2009 concerningHospitals, and Law No. 36 of 2014 concerning Health Workers, Therefore, it is time forthe government to carry out reforms in Indonesian criminal law, such as making orupdating laws and regulations regarding criminal acts or medical malpractice actionswhen a health emergency or pandemic occurs such as Covid-19, by making formulationsof criminal acts, criminal liability and sentencing precise and consistent. Second, basedon the 7 cases that have been described and based on the elements of criminalresponsibility, as well as being linked to justice regarding medical malpractice in thehandling of Covid-19 patients, they should be held criminally responsible based onarticles 359, 360 and 361 of the Criminal Code, article 79 letter C of the Law. No. 29 of2004 concerning Medical Practice, Article 126 paragraph (1) and Article 190paragraph (1 and 2) of Law No. 36 of 2009 concerning Health, and Article 84paragraph (1 and 2) of Law No. 36 of 2014 concerning Health Workers. Based on theexplanation of the 7 cases, in the absence of criminal responsibility, it can be concludedthat the main objective of the law is not achieved because there is no justice in the lawthat is created.Keywords: Covid-19, Doctors, Malpractice, Criminal Liability